2016
DOI: 10.1037/emo0000202
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of suppressing affective displays in romantic relationships: A challenge and threat perspective.

Abstract: Emotion suppression is one of the most studied topics in emotion regulation. However, little is known about how response-focused regulation strategies unfold in romantic relationships from the perspectives of both emotion regulators and their interaction partners. Using the biopsychosocial (BPS) model of challenge and threat as an organizing framework, 2 experiments examined effects of expressive suppression (vs. expression) on affective, cognitive, physiological, and behavioral processes in regulators and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 108 publications
4
87
1
Order By: Relevance
“…Figure 2 illustrates that there were a number of measures not included as too few studies were available. For example, measures of cardiac function that can be derived via impedance cardiography have received scant attention in the previous literature but provide promising results: Studies have shown that emotion regulation changed total peripheral resistance with medium to large effect sizes (Jamieson et al, 2012(Jamieson et al, , 2013Peters et al, 2014;Peters and Jamieson, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 illustrates that there were a number of measures not included as too few studies were available. For example, measures of cardiac function that can be derived via impedance cardiography have received scant attention in the previous literature but provide promising results: Studies have shown that emotion regulation changed total peripheral resistance with medium to large effect sizes (Jamieson et al, 2012(Jamieson et al, , 2013Peters et al, 2014;Peters and Jamieson, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Of those, n = 68 entered our quantitative synthesis (for an overview see Table 3). The remaining 10 studies (Delgado et al, 2008;Driscoll et al, 2009;Jamieson et al, 2012Jamieson et al, , 2013Peters et al, 2014;Baur et al, 2015;Reinecke et al, 2015;Peters and Jamieson, 2016;Zaehringer et al, 2018;Kotwas et al, 2019) were not considered, as a meta-analysis on the respective combination of emotion regulation strategy and psychophysiological measure was not possible because the number of studies was too small. See Figure 1 for a PRISMA flowchart depiction of the screening and selection of studies.…”
Section: Inclusion/exclusion Criteriamentioning
confidence: 99%
“…If social withdrawal was an evoked behavioral tendency in the severe rejection condition, participants in the inclusion condition might also have tried to reduce contact to a minimum, which would explain why we did not find differences between the inclusion and severe rejection conditions. Future studies should investigate if changes in the paradigm by touching friends or intimate partners [63] could reduce awkwardness of the situation and would lead to different behavior outcomes in the inclusion or severely rejected participant groups.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has demonstrated that instructing participants to suppress (vs. express) affective displays increases the threatening nature of relationship interactions, and thus, this manipulation should exacerbate the threat responses associated with anticipating interacting with more insecure partners. In particular, anticipating engaging in expressive suppression (vs. expression) elicits threat responses because participants anticipate the difficulty and reduced rapport associated with suppression (Peters & Jamieson, 2016). These negative consequences should be particularly problematic for individuals with partners high in attachment insecurity because engaging in expressive suppression (relative to expression) signals low desire for affiliation and may also signal dissatisfaction and unresponsiveness.…”
Section: Anticipatory Threat Prior To Dyadic Interactionsmentioning
confidence: 99%